A Study on Challenges and Issues of PRIMA - Shen, Khoo Hui; Burhan, Burhaida (Research in Management of Technology and Business, 2020)
Housing prices in Malaysia especially in urban areas have increased over the years and are affecting the lifestyle of the middle-income workers to either rent or buy houses further away from the cities. Hence, the government has taken steps to solve this issue by establishing a few affordable housing schemes which include 1Malaysia People’s Housing Program (PR1MA) that supposedly cater the housing price level for the middle-income workers. However, there are certain issues that are lingering around during the development of PR1MA, including slow delivery and land allocation which tarnishing the reputation of PR1MA. Thus, the purpose of this research is to study the process for the development of the PR1MA housing program in order to analyze the challenges and issues that come with it. This research can be achieved through content analysis and Multiple Regression Analysis (MRA). Analysis done by MRA from Statistical Package for the Social Sciences (SPSS) shows that housing criteria in Kuala Lumpur are not in line with PR1MA objectives and criteria for property type, price and location. The results are supported by analysis obtained from the content analysis, which validates the purpose of this research. Hence, by highlighting these issues, this research will hopefully can be used as guidelines to address and help overcoming these challenges for betterment of PR1MA.